HUBUNGAN ANTARA LAMA MENDERITA DIABETES MELITUS DENGAN KEKUATAN OTOT PADA PASIEN RUMAH SAKIT ROYAL PRIMA JAMBI - Nicolas Xavier Ongko (Nightingale: Journal of Nursing, 2024)
Diabetes mellitus (DM) is a chronic metabolic disease that can lead to various systemic complications, including muscle strength decline due to altered metabolism and vascular supply to muscle tissue. The duration of DM is suspected to correlate with the degree of muscle strength loss. This study aimed to examine the relationship between the duration of diabetes mellitus and muscle strength in patients at Royal Prima Hospital, Jambi. An analytical observational study with a cross-sectional approach was conducted on DM patients undergoing routine check-ups at Royal Prima Hospital. The duration of DM was obtained from medical records, and muscle strength was measured using a handgrip dynamometer. Pearson correlation test was applied to analyze the relationship between the variables. The results showed a significant negative correlation between the duration of DM and muscle strength (p < 0.05), indicating that longer disease duration is associated with reduced muscle strength. The duration of diabetes mellitus is significantly associated with a decline in muscle strength. These findings highlight the importance of early intervention in DM patients to prevent further musculoskeletal deterioration.